2020
DOI: 10.1590/1519-6984.222590
|View full text |Cite
|
Sign up to set email alerts
|

Geohelminths in the soil of the Laguna dos Patos in Rio Grande do Sul state, Brazil

Abstract: This study aimed at examining the prevalence of eggs and larvae of parasites – that may cause diseases to humans and other animals – in the soil of public squares located on the shore of Laranjal beaches, in the Laguna dos Patos, in Pelotas, Rio Grande do Sul state, Brazil. Four fieldwork trips – one per season – were taken to collect samples on six squares built on the shore of these beaches. Five samples of soil were collected on every square on every fieldwork trip. The material was processed by Caldwell &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
5
0
3
Order By: Relevance
“…Other studies conducted in soil from beaches in Brazil reported a low prevalence of parasites in these samples 6,10,17,18 , in accordance with our results. However, the data about parasitic contamination of beaches are limited in the Northern region of Brazil 17 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Other studies conducted in soil from beaches in Brazil reported a low prevalence of parasites in these samples 6,10,17,18 , in accordance with our results. However, the data about parasitic contamination of beaches are limited in the Northern region of Brazil 17 .…”
Section: Discussionsupporting
confidence: 93%
“…However, the data about parasitic contamination of beaches are limited in the Northern region of Brazil 17 . In this way, a parasitological analysis performed at the public parks onshore of beaches from Rio Grande do Sul showed 8.3% (10/120) of positivity in soil samples using the Caldwell & Caldwell's technique adapted by Pessoa and Martins (1988) 18 .…”
Section: Discussionmentioning
confidence: 93%
“…Several Brazilian researchers investigated the soils of public spaces for Toxocara eggs between 2010 and 2020 (Table 1) and almost always found high positivity rates. [18][19][20][21][22][23][24][25] Santarém et al 19 found higher numbers of Toxocara eggs in the soil of public parks with mean monthly temperatures and monthly amounts of rainfall. Queiroz et al 26 had also noticed increased soil contamination at a similar time.…”
Section: Toxocara Canis Infection In Dogs and Soil Contamination By Toxocara Eggsmentioning
confidence: 99%
“…Dogs and cats are hosts of some species of zoonotic parasites and potential transmitters of these pathogens. Considering the high numbers of these animals at home and on the streets, the human population is exposed to higher risks of parasitic infection (Leon et al, 2020). Public parks and squares are leisure environments frequently visited by the population, mainly children, and they are also easily accessed by domestic and stray animals.…”
Section: Introductionmentioning
confidence: 99%